Galur Day Old Chicken Berpengaruh pada Perbandingan Rasio Heterofil: Limfosit saat Mengalami Transportasi dari Yogyakarta ke Makassar - Indriani, Rizka; Astuti, Pudji; Husni, Amir; Airin, Claude Mona (Fakultas Peternakan Universitas Papua, 2021)
Abstract Day Old Chicken is a living commodity that is widely distributed between islands throughout Indonesia. Transport trip within two to 24 hours, depending on the distance of the enclosure to be addressed. During the Day-Old Chicken journey, a variety of stresses result in stress and also end in death. Strain Day-Old Chicken has different endurance. Physiological stress parameters in poultry by calculating the ratio of Heterophil: Lymphocytes (H: L). This study aims to determine the difference in stress between Day-Old Chicken strain Cobb and Java Super passed through. Research carried out using Day-Old Chicken strain Cobb as many as 100 chicken/box and Java Super 100 chicken /box. The transportation process from Yogyakarta airport (loading) to Makassar airport (landing). Furthermore, Day-Old Chicken was taken four animals randomly before and after it was passed for blood smear preparations. Blood smear preparations with Giemza staining to calculate the H: L ratio. Analysis of H: L ratio data as a comparison of body resistance to stress between Day-Old Chicken strain Cobb and Java Super using Two Way Anova with a 95% confidence level. The results showed that there was no interaction (P> 0.05) between location (loading-landing) and Day-Old Chicken strain different from H: L ratio. The difference in the Day-Old Chicken strain affects the H: L ratio (P <0.05) with the average value of the H: L ratio of Day-Old Chicken strain Java Super higher than the Cobb. The conclusion is that the difference in Day-Old Chicken lines that experience transportation using airplanes affects the body's resistance to stress. Keywords: Day-Old Chicken; Heterophil; Lymphocytes; Stress; Transportation Abstrak Day Old Chicken merupakan komoditas hidup yang banyak dilalulintaskan antar pulau di seluruh Indonesia. Perjalanan pengangkutan dalam waktu dua sampai 24 jam, tergantung jarak kandang yang akan dituju. Rasio Heterofil : Limfosit (H:L) dapat digunakan sebagai parameter awal adanya stress transportasi. Penelitian ini bertujuan untuk mengetahui rasio H:L serta tingkat kematian Day Old Chicken galur Cobb dan galur Jawa Super yang ditransportasikan dari Yogyakarta ke Makassar. Penelitian menggunakan Day Old Chicken galur Cobb 100 ekor/boks dan galur Jawa Super 100 ekor/boks. Proses transportasi dari bandara Yogyakarta (loading) menuju bandara Makassar (landing). Day Old Chicken diambil empat ekor secara acak sebelum dan sesudah ditransportasikan untuk perhitungan rasio H:L. Analisis data rasio H:L sebagai perbandingan ketahanan tubuh terhadap stres antara Day Old Chicken galur Cobb dan galur Jawa Super menggunakan Two Way Anova. Hasil penelitian menunjukkan bahwa tidak ada interaksi (P > 0,05) antara lokasi (loading-landing) dan galur Day Old Chicken berbeda terhadap rasio H:L. Perbedaan galur Day Old Chicken mempengaruhi rasio H:L (P < 0,05) dengan nilai rata-rata rasio H:L Day Old Chicken galur Super Jawa lebih tinggi dibandingkan galur Cobb. Kesimpulan bahwa perbedaan galur Day Old Chicken yang mengalami transportasi menggunakan pesawat terbang mempengaruhi ketahanan tubuh terhadap stres. Kata Kunci: Day Old Chicken; Heterofil; Limfosit; Stres; Transportasi.